Ex-Situ Management and Daily Behaviours of Southern Red Muntjak (Muntiacus muntjak, Zimmermann 1780) in Semarang Zoo, Central Java, Indonesia - Arini, Diah Irawati Dwi; Fitriari, Utami; Firdaus, Muhammad Fahmi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The Southern Red Muntjak, or barking deer, is widely distributed in Southeast Asia. Muntjaks are commonly raised ex-situ due to their ability to breed efficiently and adapt to diverse environmental conditions. This research aimed to evaluate ex-situ management practices and explore the daily behaviours of muntjaks in captivity. Data were collected from October to November 2023 through direct observation and interviews with the managers and zoo staff on aspects such as enclosures, diet, health mintoring, and population management. Daily behaviour data were gathered using scan sampling. Semarang Zoo has seven muntjak individuals of varying ages. The enclosure was 15 x 5 x 2 m , equipped with shelters, drinking facilities, and feeding areas. Feeding was practiced once a day. The zoo followed veterinary recommendations for diet composition, including water, spinach, papaya, banana, and cucumber. The enclosures provided ad-libitum water access and were supplemented with mineral blocks to meet mineral requirements. Zoo staff cleaned feeding areas daily, and health monitoring, including routine parasite evaluation, was performed every three months. There are 14 distinct behaviours were identified, with relaxed state or resting behaviour being the most frequent (59–69%), followed by consuming (14–20%), movement (5–6%), foraging and self-directed behaviour (2–3%), and other activities. Muntjaks exhibited heightened sensitivity to human presence, often becoming alert or running when approached or disturbed. The predominantly male population required active management to maintain reproductive success.